INTERNATIONAL RIVALRY IN THE ENERGY SECTOR: THE EASTERN EUROPEAN MARKET OF ATOMIC ENERGY IN FOCUS - Y. V. Borovsky (Vestnik MGIMO-Universiteta)
In the post-bipolar world nuclear power has become one of the areas of competition and rivalry betweenRussiaand the West. The comprehensive analysis of theoretical publications allows us to consider international competition as an abstract, depoliticized contest of states and other international actors (including companies) for some limited (mainly economic) benefits. International rivalry is more a political process, necessarily involving some rival pairs of states (or groups of states) that compete with each other not only to get some benefits, but to expand their territory or power.The competition and rivalry betweenRussiaand the West in the sphere of nuclear power are especially apparent in the Eastern European region where the American, European and Japanese corporations, with the support of the Western foreign ministries and EU institutions, try to achieve two main goals. The first goal is to win the contracts to build new power units, especially in tenders where Rosatom participates. The second goal is to become suppliers of nuclear fuel for multiple Russian- or Soviet-made VVER-type reactors, which are functioning or will be run in a number of countries in the region (Slovakia,CzechRepublic,Hungary,Bulgaria, andUkraine). Such activities can involve high risks. The West’s efforts to curb the dominant position of "Rosatom" inEastern Europeare formally associated with the need to create a "competitive market" of nuclear services in the region and to ensure the European energy security. It is also noteworthy that the expansion of Rosatom (and its predecessors) to foreign markets, including Eastern Europe, is actively supported by the Russian state which in the second half of the 1990s – after a failed attempt of following in the footsteps of the West – joined in the rivalry, mostly imposed by the U.S. and their allies.As shown by the analysis,Russiaand the West, primarily theUnited States, are involved in the nuclear power sector to advance their economic interests, expressed in the success of their national corporations. However, they are also political rivals that consider the nuclear power industry generating billions of dollars and supplying energy to many countries as one of important geopolitical resources.